The Effect of Location Selection and Store Atmosphere on Buying Interest - Muhyiddin Zainul Arifin; Mohammad Abied Aula (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
This type of research is quantitative associative. Data collection techniques using questionnaires and interviews. The respondents of this research are the customers of the Lawas Jombang coffee shop which sells 100 people. The results of the t-test research on the store atmosphere variable of 7,664 are greater than the t table of 1,667 with a significance of 0.000 less than r 0.05, the store atmosphere variable has a positive and significant effect on the buying interest variable. And the t-count value for location is 2,469, which is greater than t table for 1,667 with a sig level of 0.016 less than 0.05, so the location variable partially has a positive and significant influence on the buying interest variable. Based on the results of the F test, the calculated F value of 71.789 is greater than the F table of 3.13, meaning that the store atmosphere and location simultaneously have a positive and significant effect on the buying interest. The value of Asjusted R Square obtained is 0.682. The figure shows that 68.2% buying interest (bound variable) can be explained by store atmosphere and location. The remaining 68.2% is influenced by other factors not explained in this study. variable.